Revitalization Analysis of Forms, Songs, and Functions of Presenting Traditional Music Srawung Krumpyung in Kulon Progo Regency - Putra, Zakarias Aria Widyatama (Universitas Negeri Medan, 2023)
Traditional music Krumpyung is a local arts from Kulon Progo. The declining quality coupled with the lack of performers, containers, and limited performance time made the revitalization of Krumpyung happen. The objective of this research is to describe the result of revitalization analysis of the form, song, and function of presenting traditional music that done by Srawung Krumpyung as a step of regeneration and conservation efforts. This research is using qualitative research with narrative study and case study methods to determine that revitalization can be used as a step of regeneration and conservation efforts. Data collection technique that used in this research is snowball sampling by doing deep interview, collect data from Dinas Kebudayaan Kulon Progo Regency, or watching video documentations. The validity data form this research is measured by triangulation of sources. Data analysis technique that used in this research is interactive model by Huberman and Miles. Result of this research is revitalization can be used a step regeneration and conservation efforts by: (1) reconstruction, (2) refunctionalization, (3) representation, (4) reformation, (5) reinterpretation, (6) reorientation, and (7) recreation. The value of step regeneration and conservation efforts manifested in: (1) creativity, (2) love of the homeland, and (3) environmental care.